Enhancement of dibenzothiophene biodesulfurization by weakening the feedback inhibition effects based on a systematic understanding of the biodesulfurization mechanism by Gordonia sp. through the potential "4S" pathway. Issue 86 (1st September 2016) - Feng, Shoushuai; Yang, Hailin; Zhan, Xiao; Wang, Wu
Abstract : Gordonia sp. JDZX13 (source: industrial petroleum soil) shows good potential for dibenzothiophene (DBT) biodesulfurization. Abstract : Gordonia sp. JDZX13 (source: industrial petroleum soil) shows good potential for dibenzothiophene (DBT) biodesulfurization. With the GC/MS analysis of metabolites and PCR-sequencing verification of the key desulfurization operon ( dszA / dszB / dszC ), the valuable "4S" pathway of DBT biodesulfurization in Gordonia sp. is identified. The key rate-limiting factors (2-hydroxybiphenyl/sulfate ions) suggest significant feedback inhibition effects on cell growth ( μ x ) and biodesulfurization efficiency. Moreover, the qRT-PCR analysis of the dszA / dszB / dszC operon transcriptions also indicates the prominent negative effects on the key desulfurization enzyme activity, particularly under sulfate ion stress. Based on the abovementioned analysis, the oil/aqueous ratio in the two-phase system was optimized as 1 : 2 for better weakening of the inhibition effect, and a higher DBT removal efficiency (improved by 100.7%) was achieved. In addition, the DBT biodesulfurization mechanism is proposed. Related methods and mechanisms would be useful to further guide similar biocatalysis processes in the near future.